A note on random catalytic branching processes. (21st January 2018) - Steel, Mike; Kauffman, Stuart
Abstract: A variety of evolutionary processes in biology can be viewed as settings where organisms 'catalyse' the formation of new types of organisms. One example, relevant to the origin of life, is where transient biological colonies (e.g. prokaryotes or protocells) give rise to new colonies via lateral gene transfer. In this short note, we describe and analyse a simple random process which models such settings. By applying theory from general birth-death processes, we describe how the survival of a population under catalytic diversification depends on interplay of the catalysis rate and the initial population size. We also note how such process can also be viewed within the framework of 'self-sustaining autocatalytic networks'.